An examination of the factors determining the performance of cyclists in elite competitions - Phillips, K. E. (Victoria University, 2020)
A key objective of sports performance research is to provide team managers, coaches, and athletes seeking to improve performance with information on the attributes that contribute to or predict overall success, yet the determinants of performance in actual competition remain an under-examined and under-theorised field. The focus of this thesis is an exploration of these determinants, particularly in the more complex races that permit opponent interaction. The rationale and theoretical framework for the thesis is outlined in Chapter 1, where I explain how it is underpinned by concepts from ecological dynamics, utilising a sequential explanatory mixed-methods research approach, first to quantify the changes in cyclist performance in increasingly complex racing environments, followed by a qualitative investigation to explain and elaborate on the potential mechanisms underpinning these changes. In the initial quantitative analyses (Chapters 2 and 3), linear mixed modelling of race results was used to examine changes in the variability and predictability of elite track cyclists' performances between solo time trials and race events involving direct interaction with competitors. In Chapter 2, cyclists` performances in the three solo time-trials and three mass-start race events that comprise the overall Omnium competition were investigated. The reproducibility of performance in the mass-start events was lower than in the solo events. In Chapter 3, Match Sprint tournaments provided performance measures in a qualifying time trial and subsequent head-to-head racing. Qualifying time-trial performance largely determined success in head-to-head racing, but there was evidence of unknown factors modifying cyclists` chances of success. In Chapter 4, a systematic narrative review was undertaken, in which published findings on the determinants of cyclists` behaviours and chances of success in elite competition were collated and synthesised. Key findings were grouped and used to shape a conceptual framework of the determinants of performance. A qualitative research approach was adopted for Chapters 5 and 6, wherein semi-structured interviews with 15 elite cyclists from three racing disciplines were used to explore potential factors underpinning the results in Chapters 2, 3 and 4. Transcribed text of the interviews was examined using thematic inductive content analysis to develop initial themes, which were cross-validated with results from Chapter 4. Chapter 5 focused on the changes in the perceptions and practices of cyclists between solo time trials and race events with direct interaction between opponents. In Chapter 6, other themes of the thematic content analysis are combined with results from each prior study to propose an initial systems model of elite cycling performance, summarising the dimensions, features and mechanisms identified throughout this thesis. Final concluding statements, including the practical applications, limitations and possible future directions of this work are made in Chapter 7. In this thesis, I have demonstrated the advantages of combining research techniques and drawing on research across a range of scientific disciplines in order to enrich our understanding of competitive performance in some cycling disciplines. Research on competitive performance in other sports characterised by complex environments could benefit from this mixed-methods approach.